Academic stress in Medicine students during covid-19 pandemic - Annia Yolanda del Toro Añel; Yisel Pérez Tabío; Marlene Marina Gorguet Pí; Claudia Elizabeth Díaz del Toro (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Medical sciences students refer higher levels of academic stress, particularly those of the Medicine career. Objective: To characterize Medicine students according to stress level, psychosomatic reactions and confrontation strategies used during covid-19 pandemic. Methods: A descriptive and cross-sectional study was carried out from September to December, 2020, of 30 first and second year students of the Medicine career, belonging to Faculty No. 2 of the University of Medical Sciences in Santiago de Cuba that referred to feel nervous. The analyzed variables were sex, self-perceived level of stress, situations generating stress, physical, psychological, behavioural reactions and confrontation strategies. The percentage was used for the qualitative data, as well as the mean and the standard deviation for the quantitative ones. Results: The self-perceived level of stress was average in the male sex and high in the female sex. In the study there was a prevalence of the limited time for the realization of works, evaluations of professors and academic overload as situations generating stress; the drowsiness, restlessness, isolation and conflicts or discussions as main reactions; planning of their tasks, search of information on the situation and  assertive skill as confrontation strategies. Conclusions: The studied sample was characterized by presenting a medium level of self-perceived stress, responding to situations that generate academic stress, expressing physical, psychological and behavioural reactions when facing these situations, as well as using confrontation strategies focused on the problem.